Power Cost of an Electronic Control System for a Stance Control Knee-Ankle-Foot Orthosis - Carvajal, Federico; Reilander, Kathryn; Golkarieh, Hadi; Taebi, Saleh; Lemiare, Edward (CMBES Proceedings, 2007)
No Abstract